From Non-Brahmin Priests of the Goddess to Ascetics of God Mahima Alekha - Guzy, Lidia (Journal of the Irish Society for the Academic Study of Religions, 2016)
This article deals with Mahima Dharma a contemporary vernacular ascetic religion of Odisha/Eastern India displaying a rich diversity in its regional configurations. In this paper the author proposes to look at the main protagonists of the religion, the ascetics (babas), as non-Brahmin priests, who have incorporated shakti, the power of local goddesses into their disciplined bodies and in doing so have transformed the feminine element of the Hindu belief into the belief of the indescribable and abstract god Alekha. Mahima Dharma is seen in this contribution as a sort of micro structure on the one hand of popular asceticism in rural India and on the other hand as a recent religious reform movement integrating local non-Brahmin priesthood and the local belief in goddesses into the mainstream of the male Hindu pantheon. This article draws on the author’s PhD fieldwork research (1999-2002), published in 2002 as a monograph (Guzy 2002).